2011
DOI: 10.1509/jmr.08.0468
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: An Analysis of Profitability of Position in Online Advertising Markets

Abstract: Sponsored search accounts for 40% of the total online advertising market. These ads appear as ordered lists along with the regular search results in search engine results pages. The conventional wisdom in the industry is that the top position is the most desirable position for advertisers. This has led to intense competition among advertisers to secure the top positions in the results pages.We evaluate the impact of ad placement on revenues and profits generated from sponsored search using data for several hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
184
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(201 citation statements)
references
References 58 publications
15
184
1
1
Order By: Relevance
“…A myriad of researchers have turned to SSA data to uncover new insights about consumer search (Ghose and Yang, 2009;Rutz and Bucklin, 2011), choice and related purchasing behaviors (Jeziorski and Segal, 2009;Yang and Ghose, 2010;Agarwal et al, 2011) and advertiser/search engine strategies (Animesh et al, 2009;Yao and Mela, 2011;Rutz et al, 2012). Many of these papers have used random utility models to study the effect of ad position, keyword length, presence or absence of brand name, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of researchers have turned to SSA data to uncover new insights about consumer search (Ghose and Yang, 2009;Rutz and Bucklin, 2011), choice and related purchasing behaviors (Jeziorski and Segal, 2009;Yang and Ghose, 2010;Agarwal et al, 2011) and advertiser/search engine strategies (Animesh et al, 2009;Yao and Mela, 2011;Rutz et al, 2012). Many of these papers have used random utility models to study the effect of ad position, keyword length, presence or absence of brand name, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ghose et al (2014) show that hotels with lower customer ratings received less clicks than higher-ranked competitors. Examining an online retailing environment, Agarwal et al (2011) found that top positions had a higher CTR but this did not automatically translate into higher conversion rates. Recently, Van der Rest et al (2016) find a positive relationship between the probability that a hotel is booked and the hotel's rank on the landing page of an OTA website's customer search result.…”
Section: Introductionmentioning
confidence: 94%
“…Research has in fact shown that people avoid advertising, irrespectively of the position on the screen where the advert is placed [6].…”
Section: Introductionmentioning
confidence: 99%